The effect of habitat transformation on a twig epiphytic orchid: Evidence from population dynamics - Ospina-Calderón, Nhora Helena; Tremblay, Raymond L.; Torres, Alba Marina; Flanagan, Nicola S. (Frontiers in Ecology and Evolution, 2023)
The tropical Andean landscape has been dramatically transformed over the last century with remaining native forest limited to small fragments within a heterogeneous matrix of crops, cattle pastures, and urban environments. We aimed to explore the impact of habitat transformation on the population dynamics in an endemic twig epiphytic orchid located within the undisturbed forest and within modified matrix habitat in two regions with contrasting landscape structures: with a dominant shade coffee matrix and a dominant grassland matrix. Over two years, we surveyed 4650 individuals of the Colombian endemic orchid, Rodriguezia granadensis. We undertook four post-breeding censuses in three sites in each region in both native forest and pasture sub-sites (12 sub-sites; 48 censuses in total), and constructed demographic transition matrices (n = 36). The transition probabilities were calculated using a Bayesian approach and population grow rates were evaluated using asymptotic models and elasticities using transient dynamics. Between regions, higher population growth rate and inertia (defined as the largest or smallest long-term population density with the same initial density distribution) was seen in the shade coffee-dominated landscape. Additionally, population growth rate and damping ratio was higher in forest compared with pasture, with lower convergence time for the forest subsites. These demographic patterns reveal the contrasting levels of population resilience of this orchid in different landscape structures with the more connected shade-coffee dominated landscape permitting some healthier populations with greater population growth and survival in forest than pasture. This study highlights that twig epiphyte colonization of isolated phorophytes in pastures should not be interpreted as a sign of a healthy population but as a temporal transitory period.